1996
DOI: 10.1021/ja953282p
|View full text |Cite
|
Sign up to set email alerts
|

Double-Strand Cleavage of DNA by a Monofunctional Transition Metal Cleavage Agent

Abstract: A copper-based transition metal complex has been designed which performs double-stranded cleavage of DNA in a nonrandom fashion. The complex, ((2S,8R)-5-amino-2,8-dibenzyl-5-methyl-3,7-diazanonanedioate)copper(II), presents an ammonium group on one side of the metal equatorial coordination plane to the DNA backbone phosphate groups, while the aromatic phenylalanine-derived side chains are constrained to the opposite side of the coordination plane toward the DNA groove. This structure was designed to bind at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…In general, two mechanisms can be proposed for Cu II complexes that mediate oxidative DNA cleavage, one involving hydroxyl radicals and another involving metal-oxido species. Bocarsly et al [49,50,53] have suggested that hydroxyl radicals are generated by a variety of chemical and physical processes. Transition-metal-mediated hydroxyl radical production is known to occur by a number of routes; two well-known pathways are the Fenton and the HaberWeiss mechanism.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…In general, two mechanisms can be proposed for Cu II complexes that mediate oxidative DNA cleavage, one involving hydroxyl radicals and another involving metal-oxido species. Bocarsly et al [49,50,53] have suggested that hydroxyl radicals are generated by a variety of chemical and physical processes. Transition-metal-mediated hydroxyl radical production is known to occur by a number of routes; two well-known pathways are the Fenton and the HaberWeiss mechanism.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Characterization of the intermediates was based on Mass data. 1 H and 13 C NMR spectra were complex since there existed several conformers of N-Boc-protected tacn moieties. Figure 2 showed UV/Vis absorption titration spectrum of the Cu 2 L3 and CuL4 complexes with calf-thymus (CT) DNA at pH 7 and 25 o C. In the absence of DNA, 9-amino-acridine showed its maximum absorbance at 382 nm, 399 nm, and 420 nm and both Cu 2 L3 and CuL4 complexes at 392 nm, 411 nm, and 433 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Supercoiled plasmid DNA values were corrected by a factor of 1.3, based on the average literature estimate of lowered binding of ethidium. [64] Cleavage mechanistic investigation of pBR322 DNA was done using different reagents such as DMSO, EtOH, NaN 3 , -histidine, SOD, KI, SYBR Green, methyl green and EDTA added to pBR322 DNA prior to the addition of complexes.…”
Section: Absorption Spectroscopic Studiesmentioning
confidence: 99%